2018
DOI: 10.1002/mrd.23079
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant hesperetin improves the quality of porcine oocytes during aging in vitro

Abstract: The citrus flavonoid hesperetin has a variety of pharmacological actions, including antioxidant, antiinflammatory, and anticancer activities. This study investigated whether hesperetin prevents aging of oocytes in vitro in which it determined the maturation of nuclear and cytoplasm and the developmental capacity of embryo by modulating the reactive oxygen species (ROS) level. Porcine oocytes were matured in vitro for 44 hr (control) and for an additional 24 hr in the presence of 0, 1, 10, 100, and 250 μM hespe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 48 publications
4
20
0
Order By: Relevance
“…GSH as an endogenous antioxidant not only maintain the intracellular redox balance, but also is an indicator of cytoplasmic maturation to reflect the oocyte fertilization and subsequent development 41 . There was no reduction of GSH content for aged oocytes in this study, similar to previous reports 42 , 43 ; however, several studies have showed the aged oocytes with lower level of GSH 44 , 45 . Moreover, the aged oocytes treated with Ax exhibited an increase in intracellular GSH content, which is similar to the result of antioxidant hesperetin treatment 42 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…GSH as an endogenous antioxidant not only maintain the intracellular redox balance, but also is an indicator of cytoplasmic maturation to reflect the oocyte fertilization and subsequent development 41 . There was no reduction of GSH content for aged oocytes in this study, similar to previous reports 42 , 43 ; however, several studies have showed the aged oocytes with lower level of GSH 44 , 45 . Moreover, the aged oocytes treated with Ax exhibited an increase in intracellular GSH content, which is similar to the result of antioxidant hesperetin treatment 42 .…”
Section: Discussionsupporting
confidence: 91%
“…There was no reduction of GSH content for aged oocytes in this study, similar to previous reports 42 , 43 ; however, several studies have showed the aged oocytes with lower level of GSH 44 , 45 . Moreover, the aged oocytes treated with Ax exhibited an increase in intracellular GSH content, which is similar to the result of antioxidant hesperetin treatment 42 . The genes related to antioxidation pathway are frequently detected to evaluate the oxidative stress in aged oocytes, but different results have been obtained due to different experimental conditions.…”
Section: Discussionsupporting
confidence: 91%
“…38 Another study showed that treatment with Hesperetin could enhance the in vitro development of aging porcine oocytes and the mRNA expression of some cytoplasmic maturation marker genes, such as bone morphogenetic protein 15 (BMP15) and growth differentiation factor-9 (GDF9). 30 Our results also showed that the gene expression of PCNA, which can be found in fetal and adult ovaries of several mammals, was significantly increased by hesperidin. It has been reported that PCNA is a 36 kDa protein, which increases during the initiation of follicle growth and acts as Figure 3.…”
Section: Discussionsupporting
confidence: 68%
“…It has been found that Hesperetin can inhibit the oxidative stress via estrogen receptor-mediated actions and, as an antioxidant, it can improve the quality of porcine oocytes during aging in vitro. 30 However, based on our current knowledge, the efficiency of hesperidin on ovarian follicles in a long-term culture has not been described before. Therefore, the aim of this study was to investigate the effects of different concentrations of hesperidin on the follicular development of isolated preantral follicles in the 3D culture system made with sodium alginate hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that hesperetin has a higher bioavailability compared to hesperidin due to the rutinoside moiety attached to the flavonoid, and this seems to contribute to its superior anti-inflammatory and antioxidant properties [ 91 ]. Hesperetin is widely studied in several pathological conditions and exhibits neuroprotective effects [ 92 ], anticancer properties [ 93 ], anti-neuroinflammatory potential [ 94 ], antioxidant effects [ 95 ], and anti-inflammatory [ 96 ] activities, among others.…”
Section: Main Citrus Flavonoids With Antidiabetic Effectsmentioning
confidence: 99%